Contributions of the Pedagogical Political Project within the scope of the Monte Sinai Municipal School in Manaus (Research, Society and Development, 2022)
The theme brings with it a reflection on the contribution of the Pedagogical Political Project (PPP), which is an instrument that tends to help face the day-to-day challenges of the school in a systematic, conscious, scientific and participatory way. In this way, the general objective of this study is to analyze how the Political Pedagogical Project contributes to the daily life of the Monte Sinai Municipal School in Manaus/AM-Brazil. Methodology used was bibliographic and field, qualitative and quantitative. According to the teachers' response, it was very clear that the teacher is a fundamental part in the elaboration of the PPP, but there are still some who are resistant, and the change of paradigms is one of the aspects of the PPP. In this sense, it is up to the manager to guarantee the student an organized and quality service, so it is necessary for the manager to interact with the teachers, the team and the family. One of the biggest management challenges is still to consolidate educational practices using the PPP. The PPP is a document that must be known and accessible so that everyone involved can put it into practice. Finally, it is through the PPP that the curriculum is consolidated, as both are documents prepared collectively and gives us a direction to organize pedagogical actions in the school involving the entire school community.